(untitled) (Proceedings of the International Conference on Public Health, 2017)
This review aims to explore the potential occupational and environmental health hazards on lives of miners and neighbouring communities, in relation to bauxite mining in Malaysia. The mining related environmental issues include air, water and soil pollution due to bauxite dust; its leaching into water sources reduces soil fertility, affects agricultural food produce and aquatic life. Bauxite occupational exposure affects the health of miners, apart from negative health impacts on neighbouring communities; such as frequent respiratory symptoms, and contamination of drinking water. Other potential health effects of bauxite mining include noise-induced hearing loss and mental stress. This review describes the processes of bauxite mining, its components, the residual trace elements, and their impacts on environment and health of exposed workers and communities. It also discusses Malaysian legal requirements and occupational exposure standards for bauxite.